Escola Profissionalizante do Homem Amazônico : arquitetura sustentável em prol da inclusão socioeconômica - Silva, Isis Brito da (Brasil, 2022)
The architectural project of the Escola Profissionalizante do Homem Amazônico proposes an environment of integration of the Amazonian man with its culture, showing how rich and important it is for the region. It is proposed to invite people to stay and disseminate Amazonian customs in a conscious and sustainable way, implementing the project in an area on the edge of the Rio Negro with plenty of vegetation, with the aim of transmitting the teachings and culture in practice. With studies on the environment, educational theorists, case studies and all the necessary legislation, the school architecture project has as its main objective an inclusive and sustainable space for young people and adults in the Amazon region, with courses focused on the care and conservation of the forest and rivers, in addition to increasing income in the interior of the Amazon.